Development of a competency framework for higher education rehabilitation science administrators - Ligot, Fernando Alejandro Cruz
This study aimed to develop a competency framework that identifies the essential educational administrator competencies of rehabilitation science higher educational leaders and describes the process of the development of these essential skills. Literature on competency development of rehabilitation science higher education administrators is lacking, specifically in the Philippines. The study sought to answer the question what leadership competencies are essential for rehabilitation science higher education administrators? The researcher interviewed eight educational administrators of private and public rehabilitation science educational institutions in the country using a Constructivist Grounded Theory model of inquiry. Semi-structured interviews were conducted online via the Zoom teleconference platform from December 2021 to January 2022. The interviews were transcribed and subjected to the CGT process of analysis.